Pemahaman konsep siswa tentang pelajaran Bahasa Indonesia di kelas 1 SDN Karang Agung - Zafna Anjeli; Dessy Wardiah; Amirrudin (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to analyze the conceptual understanding of first-grade students at SDN Karang Agung in Indonesian language lessons and to identify inhibiting factors in the learning process. The research involved 24 students over five sessions using lecture methods and PowerPoint media. Test results indicate that students’ understanding of themes and the use of simple sentences still needs improvement, while their ability to identify main characters or important events is already good. However, students' understanding of punctuation remains low. The main inhibiting factors identified include low learning motivation, limited learning facilities, lack of textbooks, and less engaging teaching methods. Internal factors such as students’ psychological conditions and learning interest, as well as external factors like teaching methods, social interaction, parental support, and family economic conditions, also significantly influence learning success. This study recommends the need for more interactive learning approaches and adequate learning facilities to improve students’ conceptual understanding in Indonesian language lessons